2024
DOI: 10.1101/2024.05.21.595074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiation dermatitis in the hairless mouse model mimics human radiation dermatitis

Jessica Lawrence,
Davis Seelig,
Kimberly Demos-Davies
et al.

Abstract: Over half of all people diagnosed with cancer receive radiation therapy. Moderate to severe radiation dermatitis occurs in most human radiation patients, causing pain, aesthetic distress, and a negative impact on tumor control. No effective prevention or treatment for radiation dermatitis exists. The lack of well-characterized, clinically relevant animal models of human radiation dermatitis contributes to the absence of strategies to mitigate radiation dermatitis. Here, we establish and characterize a hairless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Cytokines including Il-1, Il-6, TNF-α, and TGF-β are produced by fibroblasts, keratinocytes, endothelial cells, and immune cells at the irradiated site to recruit immune cells to this site [ 34 ]. Studies in rodent skin demonstrate a dose-dependent increase in TGF-β following irradiation that lasts days following treatment [ 19 , 35 ]. TGF-β can recruit inflammatory cells to the skin and is involved in the tissue repair process following radiation treatment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokines including Il-1, Il-6, TNF-α, and TGF-β are produced by fibroblasts, keratinocytes, endothelial cells, and immune cells at the irradiated site to recruit immune cells to this site [ 34 ]. Studies in rodent skin demonstrate a dose-dependent increase in TGF-β following irradiation that lasts days following treatment [ 19 , 35 ]. TGF-β can recruit inflammatory cells to the skin and is involved in the tissue repair process following radiation treatment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mice were treated with a dose of 20 Gy or 30 Gy radiation to the skin surface of the right hindlimb using 6 MeV electrons (Varian 2100 iX; Varian Medical Systems, Inc., Palo Alto, CA, USA). The dose was selected based on our prior work which demonstrated that 30 Gy induces severe dermatitis and gliosis [ 19 ] in SKH-1 mice, whereas 20 Gy is associated with low grade (hair loss) cutaneous changes [ 105 ]. The radiation treatment protocol was identical to that previously published [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation